United Tastes of America: An Atlas of Food Facts & Recipes From Every State! - Bowers, Jenny; Acken, DL (Danielle L.) (London Phaidon Press Limited, 2019)
Cook around the country with this geographical collection of authentic recipes from each of the USAs 50 states, plus three territories, and the nations capital. -- publishers website.
Keywords: Cooking, American -- Juvenile literature; Food -- United States; Juvenile literature; Cooking -- United States; Juvenile literature; Cooking, American -- Juvenile literature; Food -- United States; Juvenile literature; Cooking -- United States; Juvenile literature; Cookbooks